The globalisation of Robert Lepage : Québécois cultural politics and contemporary theatre practice - Fricker, Karen Paula (Trinity College (Dublin, Ireland). Department of Drama, 2005)
This thesis is an analysis of four productions by the quebecois theatre artist Robert Lepage, and of their reception. 1 chose these productions because they broadly cover the span of Lepage's career to date (1980s: Vinci and The Dragon's Trilogy; 1990s: The Seven Streams of the River Ota; early 2000s: Zulu Time) and because they demonstrate the changing contexts in which Lepage's work has been created and received. Early on, Lepage created productions for a known, local audience, which, because they were successful locally, began to tour internationally. Now he is a major international artist making productions that tour to many countries and cultures but continvie to be created in Quebec predominantly by francophone Quebecers.
Keywords: Drama, Ph.D.; Ph.D. Trinity College Dublin